A survey on the cryptanalysis of elliptic curve cryptography - Mak, Wai Kit. (2010)
Elliptic Curve Cryptography has been introduced in the mid 1980s as a public key cryptographic system to replace block ciphers techniques. Strength of the Elliptic Curve Cryptography depends very much on the type of curve, the points and field chosen. However no known successful attacks have been made on this cryptography method till this day. Many cryptanalysis methods have been developed for Elliptic Curve Cryptography and block ciphers.Cryptanalysis for block ciphers are known to be unsuitable for Elliptic Curve Cryptography.In this report, these different types of cryptanalysis methods shall be discussed. Specific cryptanalysis methods for Elliptic Curve Cryptography and block ciphers shall be discussed in more details. Pollard's Rho cryptanalysis method for Elliptic Curve Cryptography will be program, tested and analyzed for results. Lastly, discussion on the suitability of cryptanalysis for block cipher to be used on Elliptic Curve Cryptography will be made.